Analisa Pengaruh Return on Equity (ROE) Current Ratio (CR), Debt to Equity Ratio (DER), terhadap Dividend Payout Ratio (DPR) - Misrofingah Misrofingah; Nurlelasari Ginting (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Dividend Payout Ratio is the percentage of the amount of the dividend to be paid company’s of total profits from the company to stockholders. The stockholders to invest they capital to get profits. For the company should be able to take a decision or a policy to pay dividends to stockholders or hold for reinvestment. This study aims to examine and analyze the effect of Return on Equity, Current Ratio, and Debt to Equity Ratio toward Dividend Payout Ratio in manufacture companies that listed in Indonesia Stock Exchange from 2016 to 2020. This research is quantitative research explanatory with data collection technique using a pruposive sampling. A total of 16 manufakturing firm are used as sample firm. Data analysis method used is multiple linear regression analysis. The test data used is normality test, test (t), test (f), and the coefficient of determination. The results of this research are: ROE positive effect on DPR, CR no effect on DPR, DER negative effect on DPR.